Methodical instructions to perform practical classes in the course "Hydraulics, hydraulic and pneumatic drives" - Rogovyi, Andrii; Krupa, Evgeniy Sergeevich; Rezvaya, Kseniya Sergeevna (Національний технічний університет "Харківський політехнічний інститут", 2025)
Determine the volume of water that must be additionally supplied to a water pipe with a diameter of d = 500 mm and a length of l =1 km to increase the pressure to 6 ∆=⋅ p 5 10 Pa. The pipeline is prepared for hydraulic testing and filled with water at atmospheric pressure. Deformation of the pipeline can be neglected.
Keywords: methodical instructions; practical classes; hydraulics; hydraulic drives; pneumatic drives; sectoral engineering